Acute hepatitis E infection as a cause of unexplained neurological symptoms. (17th July 2018) - Blayney, Lauren; Morrish, Paul
Abstract : Neurological disease is the most common extrahepatic manifestation of autochthonous infection with hepatitis E virus (HEV). The association between acute neurological symptoms and hepatitis E is not well known, and hence HEV testing is often omitted. This case describes aberrant neurology in a 35-year-old woman with a background of HEV infection, highlighting the need for increased awareness of acute hepatitis E infection as a cause of unexplained neurological illness.